2021
DOI: 10.1111/bjh.17934
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusion‐induced non‐transferrin‐bound iron promotes Pseudomonas aeruginosa biofilms in human sera and mortality in catheterized mice

Abstract: Transfusion of storage-damaged red blood cells (RBCs) increases nontransferrin-bound iron (NTBI) levels in humans. This can potentially enhance virulence of microorganisms. In this study, Pseudomonas aeruginosa replication and biofilm production in vitro correlated with NTBI levels of transfused subjects (R 2 = 0Á80; P < 0Á0001). Transfusion of stored RBCs into catheterized mice enhanced P. aeruginosa virulence and mortality in vivo, while pre-administration of apotransferrin reduced NTBI levels improving surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In these patients, we think that high iron entry into plasma through cellular (especially macrophage) ferroportin, finite hepatic clearance of NTBI, and finite erythroid clearance of transferrin iron together contribute to the persistence of NTBI at TSAT between 70% and 100%. Similar permissive TSAT thresholds are observed when NTBI is generated for the first time, as in myeloablation 7,8 or after transfusion of old red cells 18 …”
Section: Ntbi Relationship With Tsatsupporting
confidence: 57%
See 1 more Smart Citation
“…In these patients, we think that high iron entry into plasma through cellular (especially macrophage) ferroportin, finite hepatic clearance of NTBI, and finite erythroid clearance of transferrin iron together contribute to the persistence of NTBI at TSAT between 70% and 100%. Similar permissive TSAT thresholds are observed when NTBI is generated for the first time, as in myeloablation 7,8 or after transfusion of old red cells 18 …”
Section: Ntbi Relationship With Tsatsupporting
confidence: 57%
“…Similar permissive TSAT thresholds are observed when NTBI is generated for the first time, as in myeloablation 7,8 or after transfusion of old red cells. 18 In contrast, some studies report NTBI at lower TSAT levels >35% 19 or ≥50%. 20 For example, in HH patients undergoing sequential depletive phlebotomy, 19 or where modified proteins with high affinity for iron 11 are present in plasma, such as in diabetes.…”
Section: Ntbi Relationship With Tsatmentioning
confidence: 98%
“…These are infections in which gram-negative organisms dominate, in contrast to the gram-positive organisms implicated in many SSIs and wound-related infections [60][61][62][63][64] . Murine studies have previously identified an increased vulnerability to infection with gram-negative organisms, in particular, following transfusion 26,27,59 . This may explain why evidence of an association between transfusion and wound infection tends to be weaker 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Hemolysis releases iron into the circulation and, following transfusion of a sufficient quantity of storage-damaged red blood cells, the amount of iron released can overwhelm the capacity of transferrin (the physiologic transporter of iron in the circulation) to bind iron, leading to the presence of a pathologic form of iron, termed non-transferrin-bound iron 21-24 . Non-transferrin-bound iron has been shown to contribute to the proliferation of pathogenic bacteria both in vitro and in vivo 24-27 . Red blood cells obtained from intraoperative cell salvage (e.g., with a Cell Saver [Haemonetics]) appear to be of higher quality than those of ARBT, and transfusion of those units has not been associated with an increased risk of postoperative infectious complications 28-31 .…”
mentioning
confidence: 99%
“…Altered RBC antioxidant capacity triggers intra- [ 34 ] or extra-vascular hemolysis [ 35 , 36 ], resulting in excess circulating heme and iron [ 37 ], a phenomenon that underlies the etiology of many diseases in which oxidant stress plays a central role [ 37 ] and co-morbidities in transfusion recipients, such as acute lung injury, kidney dysfunction [ 38 , 39 , 40 ], microbiome dysbiosis [ 41 ], or septic complications in patients infected by siderophilic bacteria [ 42 ]. As such, despite intrinsic limitations of animal models [ 43 ], comparative investigations of RBC metabolism in humans and animals – where alternative strategies to cope with such stress may have evolved to regulate hemolytic propensity – can thus further our understanding of the role of (transfused) RBCs in system physiology and its pathological alterations – other than having critical direct implications for veterinary transfusion medicine purposes [ 44 , 45 , 46 , 47 ].…”
Section: Rbc Omics In Health and Disease Paves The Way For Mechanisti...mentioning
confidence: 99%